(untitled) (Annals of Medical Research, 2021)
Aim: The effects of topical antibiotics on the wound healing are one of the interesting aspects of medicine. The aim of this study is to investigate the effects of topically applied rifampicin on wound healing in skin defects.Material and Methods: Forty-two male adult Sprague Dawley rats were divided into two groups: Group A (n = 21) and Group B (n = 21). Circular full-thickness skin defects were formed in the right thoracoabdominal regions. Group A received once daily local saline and Group B received once daily rifampicin 1 cc topically applied on the wounds. The defect sizes were photographed at the baseline, and days 3, 7 and 10 and the reductions in wound sizes were measured. In each group, 7 rats were sacrificed on each of days 3, 7 and 10 and their defected region was resected. Specimens were histopathologically evaluated, and scored for inflammatory cells, collagen accumulation, granulation tissue, re-epithelialization, and features of skin defect such as what layers of the skin are affected by it, its size and whether it involves any abscess-necrosis. The results were statistically analyzed.Results: There was no statistically significant difference between groups in terms of healing rate. Comparison of scores for inflammatory cells and features of skin defect revealed statistically significant differences. Statistically significant results were obtained for collagen accumulation and granulation tissue formation in both groups. No statistically significant difference was found in re-epithelialization between the groups.Conclusion: Topically applied rifampicin in experimentally induced skin defects does not have a positive effect on wound healings.